2018
DOI: 10.1038/s41467-018-05903-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal care on gene expression and DNA methylation in a subsocial bee

Abstract: Developmental plasticity describes the influence of environmental factors on phenotypic variation. An important mediator of developmental plasticity in many animals is parental care. Here, we examine the consequences of maternal care on offspring after the initial mass provisioning of brood in the small carpenter bee, Ceratina calcarata. Removal of the mother during larval development leads to increased aggression and avoidance in adulthood. This corresponds with changes in expression of over one thousand gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 73 publications
5
50
0
Order By: Relevance
“…Drawing on quantitatively comparable methylation studies across different population structures of social insects species (26) together with new data generated in this study on normalised mass-spectrometry results obtained from the quasi-social wasp Belanogaster juncea (27), we found indeed that the typical replacement time of the queen phenotype strongly correlates with global DNA methylation levels (6,28,29), we found that global levels of DNA methylation were positively correlated with typical colony size (Fig 4D-bottom). These results support the conserved role of DNA methylation in social organisation (12,(30)(31)(32)…”
Section: Dna Methylation Contributes To Long Term Stability At the Posupporting
confidence: 79%
“…Drawing on quantitatively comparable methylation studies across different population structures of social insects species (26) together with new data generated in this study on normalised mass-spectrometry results obtained from the quasi-social wasp Belanogaster juncea (27), we found indeed that the typical replacement time of the queen phenotype strongly correlates with global DNA methylation levels (6,28,29), we found that global levels of DNA methylation were positively correlated with typical colony size (Fig 4D-bottom). These results support the conserved role of DNA methylation in social organisation (12,(30)(31)(32)…”
Section: Dna Methylation Contributes To Long Term Stability At the Posupporting
confidence: 79%
“…; Arsenault et al. ), although it is included in our Supporting Information data. There is structure present in our data due to high methylation variation between colony replicates.…”
Section: Methodsmentioning
confidence: 99%
“…We chose not to include a permutation test as part of the differential methylation analysis, as has been seen in previous research (Libbrecht et al 2016;Arsenault et al 2018), although it is included in our Supporting Information data. There is structure present in our data due to high methylation variation between colony replicates.…”
Section: Differential Methylationmentioning
confidence: 99%
“…In these species, the responsible machinery (cytosine-5 DNA methyltransferases) is absent from their genomes (Falckenhayn et al, 2016;Standage et al, 2016). When present, DNA methylation in insects contributes to diverse processes, such as nutritional control of reproductive status (Kucharski et al, 2008), development (Lyko et al, 2010;Shi et al, 2013;Yang, Guo, Zhao, Sun, & Hong, 2017), embryogenesis (Kay, Skowronski, & Hunt, 2017), alternative splicing (Bonasio et al, 2012;Flores et al, 2012;Foret et al, 2012;Libbrecht et al, 2016;Li-Byarlay et al, 2013), host-parasite evolution (Vilcinskas, 2016), memory processing (Biergans, Jones, Treiber, Galizia, & Szyszka, 2012;Lockett, Helliwell, & Maleszka, 2010), age-related changes in worker behavior (Herb et al, 2012), modulation of context-dependent gene expression (Wedd, Kucharski, & Maleszka, 2016), maternal care (Arsenault, Hunt, & Rehan, 2018), and defence against territorial intrusion (Herb, Shook, Fields, & Robinson, 2018). Perhaps most dramatically, in social insects, DNA methylation has been proposed to control the developmental path taken by a totipotent egg to either a reproductive queen or a nonreproductive worker (Herb et al, 2012;Kucharski et al, 2008;Yan, Bonasio, Simola, & Berger, 2015).…”
Section: Introductionmentioning
confidence: 99%